Pendampingan Penyelesaian Piutang Bermasalah pada Koperasi Karyawan Jayawijaya PT. KPI - Sugiyanto, Sugiyanto (LPPM Universitas Koperasi Indonesia, 2024)
This assistance was carried out as an effort to help the Koperasi Karyawan Jayawijaya PT KPI, Timika Regency, Papua. The cooperative is currently facing the problem of large amounts of account receivables, which since 2018 have not been able to be collected. The method used to resolve these problems was a participatory mentoring approach, starting with preparation and planning, implementation and evaluation. Until now, only two stages of activities have been carried out, for evaluation we are still waiting for the decision of the member meeting which will be held in March 2024. As a result of the assistance, it was agreed that the cooperative can write off problematic business receivables by writing them off completely at the end of the 2024 financial year or gradually over five (5) years, depending on the decision in the RAT. In the future, cooperatives need to anticipate by making provisions to form reserves (allowance).